Comparison of Shaping Ability between Continuous Rotary and Manual Instrumentations in Pediatric Endodontics - Güçyetmez Topal, Burcu; Falakaloğlu, Seda; Türkoğlu, Hatice (Journal of Dentistry Indonesia, 2021)
Objective: The aim of this in vitro study was to evaluate the efficacy of rotary EndoArt Ni-Ti Gold Pedo Kit and K-files in shaping ability, canal transportation, centering ability and instrumentation time in primary molars. Methods: For the study total of 30 extracted primary molars root with minimum 7mm root length were selected. Shaping of root canals in primary molars were done using the two systems, and CBCT and specialized software were used for scanning and analysis of pre-operative and post-operative to evaluate the groups for their shaping properties, apical transportation and preparation time in primary root canals. Results: No differences were found in canal transportation measures and instrumentation time between the two groups (p>0.05). The EndoArt group removed more dentin compared to K-file in all sides of the root curvature. The statistical differences were significant for coronal and middle third of the root (p<0.05). Conclusions: Under the conditions of this study, rotary EndoArt Ni-Ti Gold Pedo Kit provided more conical canals than K-files in primary teeth.